2008
DOI: 10.1007/s00011-007-7101-7
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine decreases intestinal nuclear factor kappa B activity and pro-inflammatory cytokine expression after traumatic brain injury in rats

Abstract: The results of the present study suggest that the therapeutic benefit of post-TBI glutamine supplementation might be due to its inhibitory effects on intestinal NF-kappaB activation and pro-inflammatory cytokine expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Similarly, other investigators have demonstrated that exogenous glutamine and progesterone, administered following TBI, decrease IL-1, TNF-a, and IL-6 levels in both intestinal and brain tissue (Chen, Shi, Jin, et al, 2008;Chen, Shi, Qi, et al, 2008). Since ghrelin has been shown to have antiinflammatory properties and ghrelin mediates intestinal homeostasis, it was our hypothesis that ghrelin would protect against GI dysfunction caused by TBI.…”
supporting
confidence: 52%
“…Similarly, other investigators have demonstrated that exogenous glutamine and progesterone, administered following TBI, decrease IL-1, TNF-a, and IL-6 levels in both intestinal and brain tissue (Chen, Shi, Jin, et al, 2008;Chen, Shi, Qi, et al, 2008). Since ghrelin has been shown to have antiinflammatory properties and ghrelin mediates intestinal homeostasis, it was our hypothesis that ghrelin would protect against GI dysfunction caused by TBI.…”
supporting
confidence: 52%
“…mice with the hormone ghrelin following TBI blocks the increase in TNF-a and MLCK expression along with the increase in intestinal permeability. 21 Similarly, electrical stimulation of the vagus nerve before TBI in mice, 25,26 increasing glutamine levels in the diet following TBI in rats, 27,28 or injection of the antioxidantsedative propofol following TBI in rats 29 blocks the increase in TNF-a expression as well as the increase in intestinal permeability following TBI. Conversely, mice deficient for nuclear factor erythroid 2-related factor 2 (Nrf2) have higher TNF-a expression and higher intestinal permeability than wild-type mice following TBI.…”
Section: Tbi Activates a Feedback Loop That Enhances Intestinal Permementioning
confidence: 99%
“…In animal models of sepsis, glutamine (2 to 10 mM) [19,30] has been shown to attenuate the release of proinflammatory cytokines through the inhibition of IKK (IkKa) and the subsequent downregulatory effect on the NF-kB and MAPK pathways [28], attenuating the release of IL-6 and TNF-a [19,28,[31][32][33], IL-8 [34], IL-1 b [32], and IL-10 [31]. The release of inflammatory mediators appears to be dependent on the HSP70 release, because the effect of glutamine supplementation is lost in the absence of HSP70 gene upregulation, using HSP70.1/3 knockout mice, with a subsequent uncontrolled release of TNF-a and IL-6, increasing the rate of mortality compared with normal wild-type mice [35].…”
Section: Discussionmentioning
confidence: 99%